THE DEVELOPMENT AND ADVANCEMENT OF THE SPORT OF WRESTLING (Ideal Journal of Multidisciplinary Research, 2026)
The article briefly describes the origins of wrestling and the basic rules of wrestling development.
Keywords: Wrestling, art, - sport, judo, sambo, wrestler, unique, hero, national.